Zhen-Wu-Tang Protects IgA Nephropathy in Rats by Regulating Exosomes to Inhibit NF-κB/NLRP3 Pathway - Li, Honglian; Lu, Ruirui; Pang, Yu; Li, Jicheng; Cao, Yiwen; Fu, Hongxin; Fang, Guoxing; Chen, Qiuhe; Liu, Bihao; Wu, Junbiao; Zhou, Yuan; Zhou, Jiuyao (Frontiers in Pharmacology, 2020)
Immunoglobulin A nephropathy (IgAN) is one of the most frequent kinds of primary glomerulonephritis characterized by IgA immune complexes deposition and glomerular proliferation. Zhen-wu-tang (ZWT), a well-known traditional Chinese formula has been reported to ameliorate various kidney diseases. However, its pharmacological mechanism remains unclear. Exosomes have been described in diverse renal diseases by mediating cellular communication but rarely in the IgAN. The purpose of the present study is to explore whether the underlying mechanisms of the effect of ZWT on IgAN is correlated to exosomes. Our results demonstrated that in human renal tubular epithelial cells (HK-2) stimulated by lipopolysaccharide, exosomes are obviously released after ZWT-containing serum treatment especially with 10% ZWT. In addition, once released, HK-2-derived exosomes were uptaked by human mesangial cells (HMC), which impeded the activation of NF-κB/NLRP3 signaling pathway to exert anti-inflammatory effects in a lipopolysaccharide induced proliferation model. Moreover, IgAN rat model was established by bovine serum albumin, CCL4 mixed solution and LPS. We found that 10% ZWT could significantly promote the release of exosomes from HK-2 and inhibit HMC proliferation to improve inflammation. Thus HK-2-derived exosomes treated with 10% ZWT (ZWT-EXO) were administered to the rats by tail vein injection. Our results showed that ZWT-EXO decreased the levels of 24 h proteinuria, urinary erythrocyte, IgA deposition in glomerulus and renal pathological injury which ameliorated the kidney damage. In addition, ZWT was able to dramatically promote secretion of exosomes in renal tissues while blocked NF-κB nuclear translocation as well as activation of NLRP3 inflammasome, leading to the inhibition of IL-1β and caspase-1. In conclusion, our study reveal that ZWT has protective effects on IgAN by regulating exosomes secretion to inhibit the activation of NF-κB/NLRP3 pathway, thereby attenuating the renal dysfunction. These findings may provide a new therapeutic target for the treatment of IgAN.